Susceptibility of Porphyromonas gingivalis and Streptococcus mutans to Antibacterial Effect from Mammea americana - Alejandra Herrera Herrera; Luis Franco Ospina; Luis Fang; Antonio Díaz Caballero (Advances in Pharmacological Sciences)
The development of periodontal disease and dental caries is influenced by several factors, such as microorganisms of bacterial biofilm or commensal bacteria in the mouth. These microorganisms trigger inflammatory and immune responses in the host. Currently, medicinal plants are treatment options for these oral diseases. Mammea americana extracts have reported antimicrobial effects against several microorganisms. Nevertheless, this effect is unknown against oral bacteria. Therefore, the aim of this study was to evaluate the antibacterial effect of M. americana extract against Porphyromonas gingivalis and Streptococcus mutans. For this, an experimental study was conducted. Ethanolic extract was obtained from seeds of M. americana (one oil phase and one ethanolic phase). The strains of Porphyromonas gingivalis ATCC 33277 and Streptococcus mutans ATCC 25175 were exposed to this extract to evaluate its antibacterial effect. Antibacterial activity was observed with the two phases of M. americana extract on P. gingivalis and S. mutans with lower MICs (minimum inhibitory concentration). Also, bactericidal and bacteriostatic activity was detected against S. mutans, depending on the concentration of the extract, while on M. americana extract presented only bacteriostatic activity against P. gingivalis. These findings provide important and promising information allowing for further exploration in the future.